Effect of pancreatic atrophy and hypertrophy on the small intestine. (1987) - Adler, G; Hausmann, W; Elsebach, K; Goke, B; Lorenz-Meyer, H; Herberg, L; Arnold, R
Abstract : Intestinal enzyme activities were investigated in mice with spontaneously occurring exocrine pancreatic insufficiency (EPI), in rats after induction of pancreatic insufficiency by intraductal injection of oleic acid, and in rats after feeding a proteinase inhibitor (Camostate) which induced a marked pancreatic hypertrophy. An increase in saccharase activity and in vitro uptake of L-phenylalanine was found in EPI mice, while activities of alkaline phosphatase and lactase were not altered. In oleic acid induced pancreatic insufficiency and in pancreatic hypertrophy no alterations in enzyme activities were observed. Morphometric analysis revealed no alterations in mucosal surface of EPI mice. It was suggested that the small intestine adapts fuctionally to severe and long lasting pancreatic insufficiency, but not to pancreatic hypertrophy.